Exploring Structure–Activity Relationships in Synthetic Antimicrobial Peptides (synAMPs) by a Ferrocene Scan. Issue 2 (20th September 2016) - Slootweg, Jack C.; Prochnow, Pascal; Bobersky, Sandra; Bandow, Julia E.; Metzler‐Nolte, Nils
Abstract : Synthetic antimicrobial peptides (SynAMPs) are an interesting class of novel antibiotic agents used to fight infections caused by resistant bacterial strains. Herein we report the synthesis of a ferrocene‐containing lysine (FcLys) suitable for standard Fmoc/ t Bu solid‐phase peptide synthesis. A library of (Arg‐Trp)3 ‐based antimicrobial peptides have been synthesized in which all the tryptophan residues were replaced systematically by FcLys and their biological activities evaluated. We call this technique a "ferrocene scan", in analogy with the well‐established "alanine scan" used to investigate crucial interactions in peptides. The FcLys‐peptides showed excellent activity against gram‐positive bacterial strains compared with the metal‐free parent peptide, including a four‐fold increase in activity against the resistant bacterial strain MRSA. Moreover, some members of this family of ferrocenoyl peptides also showed an up to 16‐fold increased activity compared with the parent peptide against the gram‐negative bacterium A. baumannii . This behavior distinguishes these synAMPs from the previously investigated N‐terminally ferrocenoylated peptides, which in general showed a dramatically reduced activity against gram‐negative bacteria. The FcLys‐peptides also showed low hemolytic activity against red blood cells (RBCs), which indicates excellent bacterial selectivity, making them an attractive class of novel peptide‐based organometallic antimicrobial agents. Abstract : A library of ferrocene‐substituted antimicrobials with one, two, or even three ferrocene residues in lieu of a tryptophan residue have been synthesized. The most potent compound shows a 16‐fold increased activity over the parent, metal‐free (RW)3 peptide against the A. baumannii bacteria. A four‐fold increase in activity was even observed against a multi‐resistant S. aureus MRSA strain.